FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM KEINGINAN BERBELANJA SECARA ONLINE - Riki, Riki (Jurnal Ipteks Terapan, 2017)
This study aims to analyze the factors that influence consumers in online shopping intentions. Method for the sample selection is using purposive sampling and the population is taken from member forum of trade of Facebook and Kaskus in regional Batam by total sample as much 215 respondent. The research result shows that demographics characteristics of gender have significant influence to online shopping intentions. Age have partial significant influence to online shopping intentions, whereas education, income and marital status not significant influence to online shopping intentions. Meanwhile to the medium characteristics that are perceived ease of use has a significant influence to online shopping intentions but perceived usefulness not significant influence to online shopping intentions. Perceived risk result is significant influence to online shopping intentions. Furthermore, the type of product that is partial significant to online shopping intentions, which is contained in cost outlay significant influence to online shopping intentions but tangibility not significant influence to online shopping intentions.